2005
DOI: 10.1007/s10228-005-0267-5
|View full text |Cite
|
Sign up to set email alerts
|

Larval and juvenile fishes occurring with flood tides on an intertidal mudflat in the Tama River estuary, central Japan

Abstract: Intertidal movements of fish larvae and juveniles on a mudflat in the Tama River estuary, central Japan, were investigated by comparing the abundance and sizes of fishes caught in the intertidal zone during flood tides with those in the subtidal zone during low tides. A total of 28 465 individuals, belonging to 9 families and 20 species, were collected by small purse seine. Among the abundant species, planktonic larvae and juveniles of gobiids and Konosirus punctatus were more abundant in the intertidal zone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
(14 reference statements)
1
12
0
Order By: Relevance
“…In the present study 12 species of fishes were recorded in low-tide and 31 species in high-tide conditions. The number of fish species recorded in the studied mudflat during high tide was higher than in other geographical areas, as recorded in previous studies: 22 fish species were recorded on the mudflats of Tagus estuary (Salgado et al 2004), 17 fish species on an intertidal mudflat of an Australian estuary (Morrison et al 2002), 20 in an intertidal mudflat of an estuarine system in Japan (Kanou et al 2005) and 18 in France (Amara and Paul 2003).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In the present study 12 species of fishes were recorded in low-tide and 31 species in high-tide conditions. The number of fish species recorded in the studied mudflat during high tide was higher than in other geographical areas, as recorded in previous studies: 22 fish species were recorded on the mudflats of Tagus estuary (Salgado et al 2004), 17 fish species on an intertidal mudflat of an Australian estuary (Morrison et al 2002), 20 in an intertidal mudflat of an estuarine system in Japan (Kanou et al 2005) and 18 in France (Amara and Paul 2003).…”
Section: Discussionsupporting
confidence: 66%
“…However, in addition to all the changes in environmental conditions, many species change their habitats according to their ontogeny or seasonal rhythms, which means that relations between different species and their environment or habitat are spatially and seasonally dynamic (Morrison et al 2002, Kanou et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…The total activity space used by each animal was determined for day, night, and 24 h (total) periods using minimum convex polygon analysis in the Animal Movement Extension for ArcView (Hooge and Eichenlaub 2000). Movements between positions recorded from 07:00 to 19:00 were categorized as daytime and movements between 19:00 and 07:00 were categorized as nighttime to coincide with local sunrise and sunset times.…”
Section: Activity Spacementioning
confidence: 99%
“…Several studies have demonstrated that numerous coastal and estuarine fishes move onto tidal mudflats with the rising tide and back to the subtidal zone with the ebbing tide (Morrison et al 2002;Kanou et al 2005a), because the whole substratum of these vast tidal mudflat areas is exposed at low tide, with water remaining only in isolated pools and channels. This movement of juvenile fishes is directly related to feeding dynamics and the avoidance of potential predators (e.g., Gibson et al 1996;Kneib 1997;Hampel et al 2003;Kanou et al 2005b).…”
Section: Introductionmentioning
confidence: 99%